Community Based Tourism (CBT) dalam Pengembangan Wisata Bahari di Pulau Derawan (Studi pada Dinas Kebudayaan dan Pariwisata Kabupaten Berau) - Harum Puspitasari, Laely; Hidayati, Firda; Sholihah , Qomariyatus; Iswanto, Denny (Jurnal Ilmiah Administrasi Publik, 2024)
National and regional economic recovery is still being pursued in various sectors, one of which is the tourism sector. Various strategies have been implemented to recover from the impact of the pandemic, one of which is through community empowerment through the Community Based Tourism (CBT) concept. This research aims to describe CBT in the development of marine tourism on Derawan Island. The focus of this research is analyzed using CBT theory which looks at tourism management into five main dimensions including economic, social, cultural, environmental and political. This research uses descriptive qualitative research. The research results show that various efforts have been made in developing CBT from an economic aspect in post-pandemic recovery to increase income in the tourism sector through human resource development. In the social dimension, the quality of life of the community has been improved through the empowerment of the formation of Pokdarwis. The cultural dimension has been running with the preservation of historical, culinary and dance tourist destinations. In the environmental dimension, various efforts to prevent marine abrasion still need to be improved. In the political dimension, there is a role for regional heads in developing sustainable tourism.